2003
DOI: 10.1016/s0014-4886(03)00043-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased adenine nucleotide translocator 1 in reactive astrocytes facilitates glutamate transport

Abstract: A hallmark of central nervous system (CNS) pathology is reactive astrocyte production of the chronic glial scar that is inhibitory to neuronal regeneration. The reactive astrocyte response is complex; these cells also produce neurotrophic factors and are responsible for removal of extracellular glutamate, the excitatory neurotransmitter that rises to neurotoxic levels in injury and disease. To identify genes expressed by reactive astrocytes, we employed an in vivo model of the glial scar and differential displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Previously, we observed that Ant1 is up-regulated in response to cortical lesions resulting in glial scaring [26] and that this is mediated through TGFβ-Smad signal transduction pathway [27]. To determine if Ant1 is also inducible in neurons, we used Western blots to examine the levels of Ant1 and Ant2 in culture hippocampal neurons, following 24h exposure to 100 µM glutamate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we observed that Ant1 is up-regulated in response to cortical lesions resulting in glial scaring [26] and that this is mediated through TGFβ-Smad signal transduction pathway [27]. To determine if Ant1 is also inducible in neurons, we used Western blots to examine the levels of Ant1 and Ant2 in culture hippocampal neurons, following 24h exposure to 100 µM glutamate.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Ant1, but not Ant2, is induced by brain trauma, medicated by TGFβ and the Smad pathway [26, 27]. Furthermore, it has been reported that increased expression of Ant1 achieved by transfection of cultured cells is pro-apoptotic [37].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely up-regulation of ANT1 in reactive astrocytes is associated with increased glutamate uptake. This effect seemed rather selective, as deletion of ANT1 did not alter other energy using processes, such as proliferation (Buck et al, 2003). In some studies, inhibition of mitochondrial function alone with inhibitors or by removing oxygen has no effect on glutamate uptake.…”
Section: Coupling Of Glutamate Transport To Mitochondriamentioning
confidence: 99%
“…The Glt-Gln cycle between neurons and astrocytes is a major metabolic pathway requiring B80% of the total brain glucose consumption Shen et al, 1999). Astrocytic glucose utilization increase in response to rising interstitial Glt levels and astrocytic Glt uptake decrease when ATP production fails (Buck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%